КАРБИДКРЕМНИЕВЫЙ ДЕТЕКТОРНЫЙ ДИОД Au-TiBx(ZrBx)-n-SiC 6H - Абдижалиев, С.К. (SCIENCE and SOCIETY, 2025)
In this work, the electrical parameters and characteristics of the ultrahigh frequency detector diodes Au-TiBx(ZrBx)-n-SiC 6H are presented. The possibility of using these diodes as power sensors for applications in a wide range of capacities (including power up to 1 W) has been studied.